Earnings Dynamics, Changing Job Skills, and STEM Careers. - Deming, David J; Noray, Kadeem (Quarterly Journal of Economics, 2020)
This article studies the impact of changing job skills on career earnings dynamics for college graduates. We measure changes in the skill content of occupations between 2007 and 2019 using detailed job descriptions from a near universe of online job postings. We then develop a simple model where the returns to work experience are a race between on-the-job learning and skill obsolescence. Obsolescence lowers the return to experience, flattening the age-earnings profile in faster-changing careers. We show that the earnings premium for college graduates majoring in technology-intensive subjects such as computer science, engineering, and business declines rapidly, and that these graduates sort out of faster-changing occupations as they gain experience.